EFIKASI DIRI GURU SEKOLAH DASAR INKLUSI - Helga Graciani Hidajat (Jurnal PGSD Musi, 2022)
Self efficacy is important for an inclusive primary school teacher. Self efficacy is able to assist teacher in preparing learning, teaching, and solving learning problems and facilitating learning in inclusive classes. This study aims to examine the self efficacy of inclusive primary school teachers and that factors that encourage the self efficacy of inclusive primary school teachers. This research is literature study by reviewing 18 articles from reputable journals about inclusive inclusive primary school teachers. The result of this study are the factors that influence the self efficacy of inclusive primary school teachers are the dynamics with students and teaching experience,mastery learning, teacher professionalism, positive belief in students, strategies for teaching methods and media, inclusive attitudes and outcomes of student achievement and motivation.